O Turismo é colonizador. Bases comunitárias para um turismo libertador – experiências decoloniais na Amazônia Brasileira e na Savana Africana. - Eduardo de Ávila Coelho (2022)
What is tourism? How did 'travel’ take place, and how it takes place currently? What do both – tourism and travel – have in common with colonization? How did the historical processes of formation of the modern world also constituted modern tourism? These and many other concerns arose in the mind of the researcher-traveler during trips to places that underwent the processes of 'modernization', with the arrival of the notions of 'conservation', reserves, safari, ecotourism and, with all these, the rules of management as well as tourists. Of all the destinations of this incessant journey – through America, Europe, Africa – the Amazon and Tanzania were chosen to stop for longer and deepen observation. Travel experiences overlapped in parallel research flows, which fed back into each other, as they were similar in several points: traditional communities that inhabit spaces of preserved nature transformed into protected areas (which allow these populations to remain) and where a characteristic type of tourism develops or starts to develop. A series of situations unfold from the following scenarios: Brazilian Amazon, Amanã and Mamirauá Reserves, comings and goings in the period between 2009 and 2020; Tanzania, Ngorongoro / Serengeti, during a six-month trip through Africa in 2014. Riverine people, caboclos, indigenous people, Maasai and tourists interact historically and in the eyes of the researcher-traveler, inheriting and building processes that have roots in the different colonial moments through which the two continents have passed and continue to pass. And new doubts arise: how do communities fit into these contexts? Which local cosmologies apply to the notions of nature, conservation, encounter and hospitality? How are the so-called traditional communities organized in the context of legally protected areas? In what ways does tourism affect and influence these cosmologies and relationships? What are the possibilities for local populations to appropriate the procedures and mechanisms to assert their empowerment and, thus, liberate themselves? Can tourism be a tool to liberate, or is it always an instrument to colonize? The path that inspired the research, tried to reflect on these and other questions, always trying to understand communities’ worldviews and support their initiatives.